Lu-Hf and U-Pb dating of the Zayanderud eclogites: implications for Jurassic subduction initiation along the Neotethys margin in Iran - Jamali Ashtiani, Rezvaneh; Scherer, Erik E.; Schmitt, Axel Karl; Hassanzadeh, Jamshid; Hertwig, Andreas T. (Lithos, 2024)
The time at which the Neotethys Ocean started to subduct along the southern margin of Eurasia within Iran has been debated in recent years. This margin, referred to as the Sanandaj-Sirjan Zone (SaSZ), features a series of Jurassic calc-alkaline igneous formations which were emplaced at c. 170 Ma. However, an alternative model suggests that subduction initiation occurred during the Cretaceous period. To address this age controversy, we utilized the Lu-Hf isochron method and employed SIMS U-Pb zircon and rutile geochronology to determine the metamorphic history of the earliest known Neotethyan eclogite outcrop along the upper Zayanderud River section of the SaSZ. Two eclogites separated by ∼25 km yielded Lu-Hf garnet dates of 175.1 ± 1.0 Ma and 172.5 ± 0.6 Ma. Rare <20 μm eclogitic zircon crystals in one of the eclogites are strongly zoned and yielded U-Pb dates for which a 177 ± 10 Ma rim age was deconvolved. The relatively low Dy/Yb of these zircon rims suggests that they crystallized prior to garnet formation, or retrograde in disequilibrium with garnet. Homogeneous U-Pb rutile ages averaging 162 ± 7 Ma are only marginally younger than the Lu-Hf garnet ages, consistent with the petrographic observation that rutile is predominantly found in the matrix or within garnet rims, and open-system behavior of radiogenic Pb during cooling. The newly obtained ages are close to previously published 40Ar/39Ar phengite dates and indicate a narrow time window during the Middle Jurassic for deep burial within a subduction channel, followed by eclogitization and rapid exhumation. These new constraints on the metamorphic history support subduction initiation along the SaSZ margin in the Jurassic period.